Incidence and management of neutropenia in patients undergoing the AC-T protocol in the adjuvant treatment of breast cancer (Research, Society and Development, 2021)
Breast cancer is the most common tumor among women. The introduction of adjuvant systemic antineoplastic chemotherapy has the benefits of reducing the risk of recurrence and mortality from breast cancer. However, intrinsic to all chemotherapy, adverse reactions are observed, including chemotherapy-induced neutropenia, an incident reaction clearly related to febrile neutropenia events. Such events can have a significant impact on hospital costs and compromise the objective of adjuvant chemotherapy treatment. In a cross-sectional, descriptive, quantitative and retrospective study, 289 female patients with breast cancer and undergoing systemic chemotherapy adjuvant with the AC-T protocol, were evaluated in order to describe the incidence of neutropenia and identify the managements performed to maintain the treatment use. The gross incidence of neutropenia was 52.2% during the application of CA (doxorubicin and cyclophosphamide), 26.9% during the application of T (docetaxel) in patients who did not undergo primary prophylaxis (PP), and 15, 1% during application of T at the patients who made PP. Among the identified managements, use of antibiotic therapy (25.4%), use of granulocyte colony stimulating factors (23%) and postponement of the cycle (20.3%) were the most observed. The occurrence of neutropenia events during chemotherapy for breast cancer is imminent. However, it can lead to changes in the regimen that can compromise treatment. In this study, the occurrence of neutropenia points to the need to define protocols for the use of PP and management of the adverse reaction.